2022
DOI: 10.1139/facets-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

How not to manage a pandemic, and how to recover from it: Lessons from Ecuador

Abstract: Since the initial outbreak in December 2019, the COVID-19 pandemic has resulted in more than four million deaths worldwide. Ecuador initially experienced one of the worst coronavirus outbreaks in the world. The pandemic quickly overwhelmed health care systems resulting in excess deaths of 37 000 from March to October, 2020. The public health measures taken to stop the spread of the virus had a devastating impact on the economy. There was a sharp contraction (7.8%) in Ecuador’s GDP in 2020. Furthermore, income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Telehealth was used to facilitate contact tracing and reduce the number of transmissions in health facilities. However, it is noteworthy that the ability to leverage technology and innovation is context dependent; Coral-Almeida et al’s [ 41 ] study showed how the pandemic has negatively impacted digital access through an analysis of the management and impact of COVID-19 in Ecuador. The authors noted a widening of the digital divide and a need for a policy platform that promotes digital literacy and access, particularly among less advantaged socioeconomic groups.…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth was used to facilitate contact tracing and reduce the number of transmissions in health facilities. However, it is noteworthy that the ability to leverage technology and innovation is context dependent; Coral-Almeida et al’s [ 41 ] study showed how the pandemic has negatively impacted digital access through an analysis of the management and impact of COVID-19 in Ecuador. The authors noted a widening of the digital divide and a need for a policy platform that promotes digital literacy and access, particularly among less advantaged socioeconomic groups.…”
Section: Resultsmentioning
confidence: 99%
“…The pandemic had the effect of deepening inequalities worldwide, so that if current socioeconomic structures are maintained, future crises will cause severe social disruption (Stevano et al 2021 ). Likewise, it is important to strengthen public health programs to face future health crises that could increase the vulnerability of the productive sector, considering the limited response capacity of the Ecuadorian health system during the pandemic (Alava and Guevara 2021 ; Coral-Almeida et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%